Rapid ethanol sensor based on electrolytically-exfoliated graphene-loaded flame-made In-doped SnO2 composite film - Inyawilert,K. (Elsevier, 2015)
© 2014 Elsevier B.V. All rights reserved. In this research, flame-made SnO2 nanoparticles doped with 0.2-1 wt% indium and loaded with 0.1-5 wt% electrolytically-exfoliated graphene are systematically investigated for ethanol sensing applications. The sensing films (∼10-50 μm in thickness) were prepared by spin coating technique on Au/Al2O3 substrates and evaluated for ethanol sensing performances at operating temperatures ranging from 150 to 350 °C in dry air. Characterizations by XRD, XPS, SEM, TEM and Raman spectroscopy demonstrated that In-doped SnO2 nanostructures had spheriodal morphology with polycrystalline tetragonal SnO2 phase and indium was confirmed to form solid solution with SnO2 lattice while graphene in the sensing film after annealing and testing still retained high-quality multilayer structure with low oxygen content. Gas-sensing measurement showed that SnO2 sensing film with 0.5 wt% In-doping concentration exhibited an optimal response of 110 and short response time of 2 s towards 1000 ppm C2H5OH at an optimal operating temperature of 300 °C. The additional loading of graphene at 5 wt% into 0.5 wt% In-doped SnO2 led to a drastic response enhancement to 965 with very short response time of 1.8 s and fast recovery stabilization at optimal operating temperature of 350 °C. The superior gas sensing performances of In-doped SnO2 nanoparticles loaded with graphene may be attributed to large specific surface area of the composite, high density of reactive sites of highly porous non-agglomerated graphene-SnO2 nanoparticle structure and high electronic conductivity of graphene, which allowed fast gas response and recovery. Therefore, the graphene loaded In-doped SnO2 sensor is a promising candidate for fast, sensitive and selective detection of ethanol.